GAYA HIDUP, KONSUMSI SUPLEMEN, JAMU, TANAMAN OBAT, DAN STATUS KESEHATAN LANSIA DI KABUPATEN BOGOR - Rian Diana; Katrin Roosita; Ali Khomsan (Jurnal Gizi dan Pangan, 2008)
The objective of this research was to analize the correlation of life style, supplement consumption, traditional medice, medical plants, and health status of elderly at Bogor District. The research was conducted at Ciampea Sub-district, Bogor District, West Java, from June till December 2005 using cross sectional study design. The sample size was 90 elders (45 male and 45 female). The result indicated that 3.7% sample was smoker, 17.8% sample had sport habit, and 42.2% sample had leisure activity. Only 6.7% sample consumed supplement, meanwhile the consumption of traditional medicine was 53.3% and medical plants 48.9%. The common diseases were hypertension, rheumatic and gout. The sample had a lot af health complain such as not feeling well, anemia, headache, and loin pain. Based on blood pressure measurement, 45.5% sample suffered from hypertension. The elders sport activity was negatively correlated with loin pain (p<0.05), meanwhile supplement consumption was positively correlated with constipation (p<0.01). Traditional medicine had a positive correlation with age (p<0.01) and negative correlation with loin pain (p<0.05). Medical plants had a positive correlation with decreased appetite (p<0.01), chewing difficulties (p<0.01) and decreased sense of smell (p<0.01).